Sexualised Music Videos Broadcast on Australian Free-to-air Television in Child-friendly Time Periods. (14th April 2015) - Ey, Lesley-anne; McInnes, Elspeth
<x content-type="archive" xml:space="preserve">Abstract</x> Although many researchers have demonstrated that music videos contain high levels of sexual connotation, none have specifically investigated music videos accessible to young children. This study analysed 405 individual music videos broadcast on Australian free-to-air television in time periods classified PG/G to identify the types and frequency of sexualised display. Results showed that these music videos contained relatively high levels of sexualised content, with particular genres and artists displaying higher levels of sexualised material. The findings indicate a need for a review of the current Australian classification system.